RHX Dating of Archeological Ceramics Via a New Method to Determine Effective Lifetime Temperature. Issue 3 (29th November 2014) - Moinester, Murray; Piasetzky, Eli; Braverman, Michael
Abstract : Determining the absolute chronology of ceramic artifacts has significant implications for archeological and historical research. Wilson, Hall et al . recently suggested a new technique for direct absolute dating of archeological ceramics based on a moisture‐induced chemical reaction, called rehydroxylation (RHX) dating. RHX dating proceeds by measuring the mass of chemically combined water in the ceramics in the form of OH hydroxyls, and the mass gain rate at the Effective Lifetime Temperature (ELT) that the ceramics experienced over its lifetime. To date, ELT determinations have been based on estimates of the ceramic's lifetime temperature history; taking into account weather and climate data and the depth at which the artifact was found. The uncertainty in determining the ELT can be a major component of the overall dating uncertainty. Here, we propose an alternative method which relies minimally on weather and climate data, and provides more precise determinations of the ELT and the ceramic age . The proposed method (SAS: Same Age Samples) involves a minimum of four measurements of the RHX mass gain rate constant for two ceramic samples of the same age at two temperatures. We show via simulations that the proposed SAS method can determine the ELT with a precision of 0.2 K which is comparable to the best ELT determination based on lifetime temperature history, and also comparable to available microbalance temperature resolutions of around 0.1 K. The corresponding percent age error is then 1.4%, or 43 yr for a 3000‐yr‐old ceramic. The proposed SAS method should be tested with ceramic samples of different ages, whose ELT are well‐known.